ChemInform Abstract: Unique Structure and Solute ‐ Solvent Interaction in Imidazolium Based Ionic Liquids. Issue 41 (19th September 2013) - Gonfa, G.; Bustam, M. A.; Man, Z.; Abdul Mutalib, M. I.
Abstract Review: 100 refs.